Health Facilities’ Readiness to Manage Hypertension and Diabetes Cases at Primary Health Facilities in Bidibidi Refugee Settlement, Yumbe District, Uganda - Vuchiri Ray Isadru; Rose Clarke Nanyonga; John Bosco Alege (Journal of Tropical Medicine)
Background. NCDs are the greatest global contributors to morbidity and mortality and are a major health challenge in the 21st century. The global burden of NCDs remains unacceptably high. Access to care remains a challenge for the majority of persons living with NCDs in sub-Saharan Africa. In Uganda, 55% of refugee households, including those with chronic illnesses, lack access to health services. Of these, 56% are in the West-Nile region where the Bidibidi settlement is located, with 61% of its refugee households in need of health services especially for NCDs (UNHCR, 2019). Data on NCDs in Bidibidi are scarce. Unpublished health facilities’ (HFs) data indicate that cardiovascular diseases (CVDs) (54.3%) and metabolic disorders (20.6%) were the leading causes of consultation for major NCDs (IRC, 2019). No readiness assessment has ever been conducted to inform strategies for the efficient management of NCDs to avert more morbidity, mortality, and the economic burden associated with NCD management or complications among refugees. This study sought to determine the readiness of HFs in managing hypertension (HTN) and diabetes cases at primary health facilities in the Bidibidi refugee settlement, Yumbe district, Uganda. Methods. The study used facility-based, cross-sectional design and quantitative approach to assess readiness for the management of HTN and diabetes. All the 16 HFs at the Health Centre III (HCIII) level in Bidibidi were studied, and a sample size of 148 healthcare workers (HCWs) was determined using Yamane’s formula (1967). Proportionate sample sizes were determined at each HF and the simple random sampling technique was used. HF data were collected using the Service Availability and Readiness Assessment (SARA) checklist and a structured questionnaire used among HCWs. Data were analyzed using SPSS version 20. Univariate analysis involved descriptive statistics; bivariate analysis used chi-square, Fisher’s exact test, and multivariable regression analysis for readiness of HCWs. Results. 16 HCIIIs were studied in five zones and involved 148 HCWs with a mean age of 28 (std ±4) years. The majority 71.6% (106) were aged 20–29 years, 52.7% were females, and 37.8% (56/148) were nurses. Among the 16 HFs, readiness average score was 71.7%. The highest readiness score was 89.5% while the lowest was 52.6%. The 16 HFs had 100% diagnostic equipment, 96% had diagnostics, and 58.8% had essential drugs (low for nifedipine, 37.5%, and metformin, 31.2%). Availability of guidelines for the management of HTN and diabetes was 94%, but only low scores were observed for job aid (12.5%), trained staff (50%), and supervision visits (19%). Only 6.25% of the HFs had all the clinical readiness parameters. On the other hand, only 24% (36) of the HCWs were found to be ready to manage HTN and diabetes cases. Chi-square tests on sex (p<0.001), education level (p=0.002), and Fisher’s tests on profession (p<0.001) established that HCWs with bachelor’s degree (AOR = 3.15, 95% CI: 0.569–17.480) and diploma (AOR = 2.93, 95% CI: 1.22–7.032) were more likely to be ready compared to the reference group (certificate holders). Medical officers (AOR = 4.85, 95% CI: 0.108–217.142) and clinical officers (AOR = 3.79, 95 CI: 0.673–21.336) were more likely to be ready compared to the reference group, and midwives (AOR = 0.12, 95% CI: 0.013–1.097) were less likely to be ready compared to the reference group. In addition, female HCWs were significantly less likely to be ready compared to male HCWs (AOR = 0.19, 95% CI: 0.073–474). Conclusion. HFs readiness was high, but readiness among HCWs was low. HFs had high scores in equipment, diagnostics, and guidelines, but essential drugs, trained staff, and supervision visits as well HCWs had low scores in trainings and supervisions received. Being male, bachelor’s degree holders, diploma holders, medical officers, and clinical officers increased the readiness of the HCWs.